2006
DOI: 10.1038/ncb1531
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VI targeting to clathrin-coated structures and dimerization is mediated by binding to Disabled-2 and PtdIns(4,5)P2

Abstract: Vesicle transport is essential for the movement of proteins, lipids and other molecules between membrane compartments within the cell. The role of the class VI myosins in vesicular transport is especially intriguing because they are the only class that has been shown to move "backwards" towards the minus end of actin filaments1. Myosin VI is found in distinct intracellular locations and implicated in processes such as endocytosis2,3, exocytosis, maintenance of Golgi morphology4,5 and cell movement6. We have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
238
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(247 citation statements)
references
References 28 publications
8
238
0
Order By: Relevance
“…To verify the novel MYO6 interaction network, we introduced mutations into the known cargo‐binding and lipid‐binding sites, the WWY, RRL and PIP 2 binding motifs 10, 11, 14 and assessed differences in the relative abundance of BirA*‐MYO6 binding partners using a SILAC‐based approach (Fig 1F). Analysis of these cells by confocal microscopy also revealed that the ΔRRL and ΔPIP2, but not the ΔWWY mutation, perturbed MYO6 targeting to APPL1 endosomes (Fig EV1A).…”
Section: Resultsmentioning
confidence: 99%
“…To verify the novel MYO6 interaction network, we introduced mutations into the known cargo‐binding and lipid‐binding sites, the WWY, RRL and PIP 2 binding motifs 10, 11, 14 and assessed differences in the relative abundance of BirA*‐MYO6 binding partners using a SILAC‐based approach (Fig 1F). Analysis of these cells by confocal microscopy also revealed that the ΔRRL and ΔPIP2, but not the ΔWWY mutation, perturbed MYO6 targeting to APPL1 endosomes (Fig EV1A).…”
Section: Resultsmentioning
confidence: 99%
“…Other proteins showed a similar pattern of biphasic recruitment and thus defined a dynamin module. These included actin-binding proteins such as the actin-and clathrin-binding protein Hip1R [44] as well as the motor protein myosin6, which binds actin and the adaptor protein Dab2 [45]. Other proteins involved in actin dynamics and grouped in the dynamin module included the Arp2/ 3 activator N-WASP [46,47], Eps8, an actin capping protein that forms a complex with Abi1 and binds N-WASP [33] and the motor protein myosin1E [48].…”
Section: The Dynamin/myosin Modulementioning
confidence: 99%
“…The myosin VI binding region of human Dab2 is outside of the conserved phosphotyrosine-binding domain, and the residues critical for binding (46) do not appear to be in the Dab sequence. In addition, Drosophila M6 contains LWY in the position of the WWY motif required for Dab2 binding (47); therefore, an interaction between the Drosophila proteins is not necessarily expected.…”
Section: Discussionmentioning
confidence: 99%